Individual Worth vs. Aggregate Value: Influential Factors of Non-Market Works (NMWs) in Bangladesh (Global Journal of Management and Business Research, 2012)
The national accounts appear to be saying that the NMWs are worth nothing; but, in reality, the NMWs increase the value of purchased goods and services and contribute to the formation and development of human resources. Abdel, et al. (1969), Chadeau, (1992), Hamdad, (2003), Charmes, (2006) put their effort to evaluate the NMWs for their respective countries by introducing satellite account and finally comparing with the national account. Although the processes of evaluation of the NMWs are difficult task, here two methods, such as works method and opportunity cost method, have been incorporated to evaluate the NMWs in Bangladesh. To know individual worth to producing NMWs and to discover the method of estimation of the NMWs, this study presents the idea of our economy which is always undermined by the conventional market framework. This study is principally based on primary data and case studies. To know the contribution of different groups of people who produce NMWs, this research concentrates on aggregate output of the value of NMWs. This study find that earning member, total hours of NMWs, estimated total support and employment status were the significant determinant to evaluate the aggregate value of NMWs. Two models were considered based on two methods of estimation. Both of the models signify the said independent variables. By taking rational figures (available information on field research) against the independent variables, this research uncover that tk.2,714 person/per month and tk. 2,317 person/month were produced by works method and opportunity cost method respectively.